Propuesta para la creación de un centro de facilitación turística y adecuación del sendero existente en el mirador de la ciudadela el paraíso de la ciudad de Guayaquil - Bastidas Andrade, Ma. Isabel (2009)
“Proposal of the creation of a Facilities Center and the adaptation of the existing path in El Paraiso, in the city of Guayaquil”, presents the feasibility study to integrate the proposal to the tourist product of Guayas province, specifically in Guayaquil. We have developed five chapters detailed below. The first chapter talks about the general information of the region; its origins, geographic situation, natural characteristics, demographic studies, and the existing infrastructure.The second chapter describes the analysis of the tourist market of the city and its demand. Marketing strategies are outlined before positioning our product in the market, concluding with the SWOT analysis. The third chapter involves the technical description of the facilities and the path; activities to develop; and services to be offered. It details the required equipment, the area design and environmental impact. The fourth chapter describes the organizational structure, detailing the job descriptions, commercial strategy, and the marketing plan. The fifth chapter corresponds to the financial studies, analyzing the investment, costs, financial plans, and the cost-benefit analysis to obtain the feasibility of the project through the income statement projection. Last but no least, the conclusions and recommendations about the realization of the project, are made.